2005
DOI: 10.1073/pnas.0502323102
|View full text |Cite
|
Sign up to set email alerts
|

Laser-capture microdissection of plasma cells from subacute sclerosing panencephalitis brain reveals intrathecal disease-relevant antibodies

Abstract: Increased IgG and oligoclonal bands (OGBs) are found in the cerebrospinal fluid (CSF) of humans with chronic infectious CNS diseases such as neurosyphilis, cryptococcal and tuberculous meningitis, Lyme disease, some viral meningitides, varicella zoster virus vasculopathy, and subacute sclerosing panencephalitis (SSPE), a chronic encephalitis caused by measles virus (MV). Studies in which the specificity of CSF OGBs was analyzed showed that the antibodies were directed against the agent that causes disease (1-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 29 publications
(22 reference statements)
1
53
0
Order By: Relevance
“…PCR-amplified Ig H and L chain genes from each plasma cell clone were used to recombinantly reconstruct the antigen specificity of antibodies expressed by cePC preserving the original Ig H and L chain pairings of individual plasma cells. This approach has been demonstrated to faithfully resurrect pathogen-specific antibodies from individual plasma cells from patients with subacute sclerosing panencephalitis [25] and borreliosis, and to maintain the original antibody affinity [26].…”
Section: Clonally Expanded Plasma Cells In the Csf Of Ms Patientsmentioning
confidence: 99%
“…PCR-amplified Ig H and L chain genes from each plasma cell clone were used to recombinantly reconstruct the antigen specificity of antibodies expressed by cePC preserving the original Ig H and L chain pairings of individual plasma cells. This approach has been demonstrated to faithfully resurrect pathogen-specific antibodies from individual plasma cells from patients with subacute sclerosing panencephalitis [25] and borreliosis, and to maintain the original antibody affinity [26].…”
Section: Clonally Expanded Plasma Cells In the Csf Of Ms Patientsmentioning
confidence: 99%
“…This approach is particularly useful in recapitulating in vitro the intrathecal antibody response in human CNS inflammatory diseases. Our previous sequence analysis of H-and L-chain V regions of plasma cells microdissected from SSPE brain revealed features of a targeted antigen-driven response, including clonal expansion, somatic mutation, intraclonal variation, and receptor editing (3). Furthermore, we demonstrated that the antibody response in SSPE brain is directed largely against MV, particularly the N protein, as evidenced by the specificity of five of eight rAbs generated from SSPE brain plasma cell clones.…”
Section: Discussionmentioning
confidence: 99%
“…Full-length human IgG1 rAbs were produced in mammalian tissue culture cells (Invitrogen, Carlsbad, Calif.) from V region sequences of expanded SSPE brain plasma cell clones as described previously (3). Briefly, V H regions were cloned into pIgG1Flag, a modified version of the episomal expression vector pCEP4 (Invitrogen) that contains a full-length human IgG1 C region domain and a C-terminal Flag epitope (21).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abs to certain microbial Ags can dominate the immune response. For example, Burgoon et al (9,10) prepared synthetic Abs from overrepresented IgG sequences in the brains of patients with subacute sclerosing panencephalitis (SSPE) and demonstrated that all of the synthetic Abs that bound to SSPE brain tissue reacted with measles virus nucleocapsid.…”
Section: Discussionmentioning
confidence: 99%